Primary trigeminal neuralgia is associated with posterior fossa crowdedness: A prospective case-control study. (January 2018) - Cheng, Jian; Meng, Jinli; Liu, Wenke; Zhang, Heng; Hui, Xuhui; Lei, Ding
Highlights: The mean PFCI is significantly higher in patients with TN than in controls. Women have a more crowded posterior fossa than men. Age is negatively correlated with the PFCI. Women, younger age and TN disease are associated with a higher PFCI. Abstract: Neurovascular conflict (NVC) has been postulated to be the underlying cause of trigeminal neuralgia (TN). Does the posterior fossa crowdedness increase the chance of NVC? The aim of this study was to quantitatively measure the posterior fossa crowdedness in patients with TN and to perform a comparison with healthy controls. We conducted a prospective case-control study of 46 patients diagnosed with primary TN and 46 sex- and age-matched healthy controls. All subjects underwent high-resolution three-dimensional MRI, and the 3D Slicer software was used to measure the posterior fossa volume (PFV) and hindbrain volume (HBV). The posterior fossa crowdedness index (PFCI) was calculated as HBV/PFV × 100%. The results showed that patients with TN had a larger HBV (155.4 ± 23.2 cm 3 versus 152.9 ± 13.5 cm 3, P = .16) and a smaller PFV (182.7 ± 18.3 cm 3 versus 186.1 ± 11.7 cm 3, P = .42) as compared to control subjects, but these values were not significantly different. The mean PFCI was significantly higher in patients with TN than in controls (85.1% ± 3.4% versus 82.2% ± 5.3%; P = .03). Women had a more crowded posterior fossa than men (85.8% ± 2.1% versus 84.1% ± 2.6%; P = .023) in patients with TN. The correlation analysis showed that a higher PFCI was associated with younger age (P = .02), woman (P = .014), and TN disease (P = .001). From this study, we conclude that patients with TN have a more crowded posterior fossa than healthy subjects. Women, younger age and TN disease are associated with a higher PFCI. The posterior fossa crowdedness may be a risk factor of NVC, and thus more likely to result in the genesis of TN.